The Birth of a New Extrusive Dome of the Sheveluch Volcano (Kamchatka) in 2024 According to Continuous Satellite Monitoring in the VolSatView Information System - Girina O.A.; Manevich A.G.; Loupian E.A.; Melnikov D. V.; Nuzhdaev I.A.; Uvarov I.A.; Romanova I.M.; Sorokin A.A.; Kramareva L.S.; Nuzhdaev A.A. (Springer, 2024)
Sheveluch is one of the most active volcanoes in Kamchatka. Its modern edifice includes three main elements: Old Sheveluch, an ancient caldera and Young Sheveluch. On the southeastern slope of Old Sheveluch, there is a group of ancient extrusive domes (from south to north): Sherokhovataya, Krasnaya, Karan, and Sopochka na sklone. Only in the area of the Karan dome are there heated areas with mofets temperature of 70–96°C. After the powerful explosive eruption of the Sheveluch volcano in April 2023, the gas–steam activity of the Karan dome intensified, and a thermal anomaly began to be noted in satellite images of the area of this dome. On April 26, 2024, in a JPSS-1 satellite image at 15:07 UTC, Kamchatkan Volcanic Eruption Response Team scientists discovered a bright thermal anomaly in the area of the Karan dome; that is, they recorded a unique phenomenon on this day: the birth of a new volcanogenic formation – the new lava dome. It was given the name 300 years of the Russian Academy of Sciences. As of June 7, 2024, the size of the new dome was 800 × 500 m and the area of the dome crown was 0.19 km2. The eruption of the new lava dome 300 Years of the Russian Academy of Sciences is continuing.
Keywords: 20.23.25 Информационные системы с базами знаний; 38.37.25 Вулканология; Шивелуч